The Philosophy of International Law. - Besson, Samantha; Tasioulas, John. (Oxford : OUP Oxford, 2010)
International law has recently emerged as the subject-matter of an exciting new field of philosophical investigation. The Philosophy of International Law contains 29 cutting-edge essays by leading philosophers and international lawyers, all published here in English for the first time, that address the central philosophical questions about international law. The volume's overarching theme is the moral and political values that should guide the assessment and development of international law and institutions. Some of the essays tackle general topics such as the sources and legitimacy of interna.
Contents; Contributors; Acknowledgements; Preface; Introduction; PART I: GENERAL ISSUES IN THE PHILOSOPHY OF INTERNATIONAL LAW; PART II: SPECIFIC ISSUES IN THE PHILOSOPHY OF INTERNATIONAL LAW; Index.
Includes bibliographical references and index.
Keywords: International law -- Philosophy; Law -- Philosophy; International law -- Philosophy; Law -- Philosophy; Electronic books